2020
DOI: 10.1111/and.13715
|View full text |Cite
|
Sign up to set email alerts
|

Expression of RXFP2 receptor on human spermatozoa and the anti‐apoptotic and antioxidant effects of insulin‐like factor 3

Abstract: Insulin-like peptide 3 (INSL3) belongs to the large family of peptide hormones called 'insulin relaxin' (Shabanpoor et al., 2011). INSL3 is secreted by testicular Leydig cells as a marker for the complete differentiation of adult Leydig cells in men and all mammalians that mediates the descent of the testicle during the embryonic period and, as a paracrine factor, mediates gonadotropin activity in adults (Anand-Ivell et al., 2006; Muda et al., 2005). This hormone binds to the RXPF2 receptor and plays an import… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 32 publications
(48 reference statements)
0
4
0
Order By: Relevance
“… Schematic illustrations of RXFP2 localization and the roles of INSL3 in testicular tissue. 9 , 27 , 55 , 56 , 63 , 64 , 65 , 66 , 67 BV, blood vessel; INSL3, insulin‐like peptide 3; LHR, luteinizing hormone receptor; Ly, Leydig cell; RS, round spermatid; S, spermatozoon; Sc, spermatocyte; Sg, spermatogonia; Sr, Sertoli cell; T, testosterone …”
Section: Insl3 Structure Expression Receptor and Rolesmentioning
confidence: 99%
See 2 more Smart Citations
“… Schematic illustrations of RXFP2 localization and the roles of INSL3 in testicular tissue. 9 , 27 , 55 , 56 , 63 , 64 , 65 , 66 , 67 BV, blood vessel; INSL3, insulin‐like peptide 3; LHR, luteinizing hormone receptor; Ly, Leydig cell; RS, round spermatid; S, spermatozoon; Sc, spermatocyte; Sg, spermatogonia; Sr, Sertoli cell; T, testosterone …”
Section: Insl3 Structure Expression Receptor and Rolesmentioning
confidence: 99%
“… 66 The addition of INSL3 to human sperm reportedly reduced oxidative stress and enhanced their motility. 67 The abovementioned studies advocate considerable functions of INSL3 in testicular spermatogenesis and steroidogenesis in animals, but not for humans. Direct effects of INSL3 on sperm functions remain to be determined in every species in spite of the receptor's expression on sperm in some animals.…”
Section: Insl3 Structure Expression Receptor and Rolesmentioning
confidence: 99%
See 1 more Smart Citation
“…There is some evidence to suggest that RXFP2 may also be expressed in or on free spermatozoa (Feugang et al, 2011(Feugang et al, , 2015Pitia et al, 2017;Shokri et al, 2020), or on cells of the epididymal epithelium (Anand-Ivell et al, 2006b;Filonzi et al, 2007), from where it might be transferred to transiting or stored sperm by transcytosis of epithelial vesicles. Effects of INSL3 on ejaculated sperm function have also been shown for the human, but only at very high, supraphysiological INSL3 concentrations (Shokri et al, 2020), so that a natural role in vivo must be doubted. Our own studies using human sperm indicated no effect at physiological concentrations (unpublished).…”
Section: Insl3 and Spermatogenesismentioning
confidence: 99%